The Impact of Flexitime on Employee Attitudes - Hicks, William D.; Klimoski, Richard J. (Academy of Management Journal, 1981)
This investigation of flexitime did not support the traditional flexitime consequences for work satisfaction or leisure satisfaction. However, employees working under a flexitime schedule reported certain other improvements, including easier travel and parking, a smaller amount of interrole conflict, a greater feeling of being in control in the work setting; and more opportunity for leisure activities.